Corpus-based exploration of linking adverbials of result: discovering what ELT writing coursebooks lack - Supakorn Phoocharoensil, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The purpose of this study was to examine four linking adverbials (LAs) of result, which are THUS, THEREFORE, HENCE, and SO, in the Corpus of Contemporary American English (COCA), focusing on written academic English. The data was collected from 1,200 concordance lines of the target LAs randomly selected from ACADEMIC genre in COCA. The findings revealed that the most frequent LA was THUS. The second and third most common were THEREFORE and HENCE respectively, while the SO occurred with the least frequency. With regard to the patterns in which these LAs are used, contrary to prior studies that reported SO to be the most frequently occurring in spoken English in the initial position, over 90% of SO in academic written English was found in the middle position. The patterns of the other target LAs in the corpus-informed data also outnumbered those available in the surveyed ELT coursebooks. Pedagogically speaking, it is highly recommended that English teachers incorporate more salient LA patterns based on authentic corpus-based data into their lessons to enhance the textbook information.